2022
DOI: 10.1101/2022.12.08.519509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell type-specific disruption of cortico-striatal circuitry drives repetitive patterns of behaviour in fragile X syndrome model mice

Abstract: Individuals with fragile X syndrome (FXS) are frequently diagnosed with autism spectrum disorder (ASD), including increased risk for restricted and repetitive behaviours (RRBs). Consistent with observations in humans, FXS model mice display distinct RRBs and hyperactivity that are consistent with dysfunctional cortico-striatal circuits, an area relatively unexplored in FXS. Using a multidisciplinary approach, we dissected the contribution of two populations of striatal medium spiny neurons (SPNs) in the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…In contrast, Naaijen et al (2017) found no differences in striatal activity between autistic children and children with OCD, despite significantly greater compulsivity amongst autistic children. Several previous studies have also highlighted links between striatal activity and repetitive behavior, though much of this research has been conducted using animal models (e.g., Longo et al, 2022;Muehlmann et al, 2020). To better understand the links between neurological factors and manifestations of repetitive behavior, more studies assessing repetitive behaviors as a multidimensional construct are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Naaijen et al (2017) found no differences in striatal activity between autistic children and children with OCD, despite significantly greater compulsivity amongst autistic children. Several previous studies have also highlighted links between striatal activity and repetitive behavior, though much of this research has been conducted using animal models (e.g., Longo et al, 2022;Muehlmann et al, 2020). To better understand the links between neurological factors and manifestations of repetitive behavior, more studies assessing repetitive behaviors as a multidimensional construct are needed.…”
Section: Discussionmentioning
confidence: 99%
“…FXS is a genetic form of intellectual disability and ASD characterized by the genetic inactivation of Fmrp, encoding for an RNA-binding protein that represses the translation of a specific subset of mRNAs associated with eIF4E. Thus, FXS model mice exhibit increased eIF4E-dependent protein synthesis along with hyperactive mTOR signaling 83,84 . The dysregulated protein synthesis is accompanied by diminished evoked DA release detected by FSCV in acute corticostriatal slices 85 and behavioral inflexibility in a touchscreen operant task 86 .…”
Section: Discussionmentioning
confidence: 99%
“…Acute PERK inhibition, although not tested in TSC mouse models, has been shown to improve cognitive function by boosting translation output 57,58 . On the other hand, chronic PERK inhibition is associated with impaired behavioral flexibility and working memory deficit 59,60 . Hence, we asked whether subchronic inhibition of either mTORC1 or PERK could rescue stress-precipitated anxiety in Tsc2 cHET males and social avoidance in cHET females.…”
Section: Mainmentioning
confidence: 99%